Meditative Listening in the Pāli Buddhist Canon - Giustarini, Giuliano (2023)
This article addresses the intersection of the oral tradition with textual contents in Pāli Buddhist literature, by focusing mostly on the Suttapiṭaka. Lexicon and stylistic features can be seen as intentional strategies to enhance specific mnemonic and meditative qualities in the disciples, thus working symbiotically with the instructions they convey. By examining selected passages, I will demonstrate a functional interrelationship of three main factors: the lexicon of listening, the emphasis on attention, and meditative instructions. These three factors, in turn, rely upon the authoritative power of the scriptures, which is constructed and reinforced with specific rhetorical stratagems to raise and enhance meditative qualities in the disciples.
Keywords: Meditation; Orality; Pāli Canon; Buddhism